Effect of COVID-19 travel restrictions on Phoenix air quality after accounting for boundary layer variations. (April 2021) - Miech, Jason A.; Herckes, Pierre; Fraser, Matthew P.
Abstract: Due to the global response to the COVID-19 pandemic, there have been a variety of policy responses that have produced a range of expected and unexpected effects on society and our surrounding environment. One widely reported result of the pandemic response is that travel restrictions have resulted in improvements in regional air quality. This study aims to determine the effect of COVID-19 related Stay at Home precautions on air quality in a metropolitan area. We specifically focus on CO, NO2, and PM10 in Maricopa County (Phoenix), Arizona, as these all contribute to local air quality concerns. The role of meteorological parameters on ambient concentrations for these pollutants was investigated by using the local planetary boundary layer height (PBH) to account for vertical mixing. Across all three sites studied, there was no uniform decrease in either CO or NO2, even when freeway traffic volume was down by ~35%. For PM10, there was a significant decrease of ~45% seen at all the sites for the period most directly impacted by local Stay at Home restrictions compared to the past two years. This indicates that different pollutants have fundamentally different behavior in the local environment and suggests that these pollutants originate from different sources. Graphical abstract: Image 1 Highlights: Planetary boundary layer height impacts ground level CO and NO2 concentrations. No reduction in NO2 and CO due to COVID-19 travel restrictions. COVID-19 travel restriction period experienced a 45% decrease in PM10 . Impact of COVID-19 travel restriction on pollutant dependent on formation mechanism.